2022
DOI: 10.1039/d2ee00568a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic limitations on alkane dehydrogenation under H2deficient conditions relevant to membrane reactors

Abstract: Experimentally simulating H2 removal during catalytic ethane dehydrogenation indicates that ethylene yields may be limited due to coking reactions, and accelerated coking causes more rapid catalyst deactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…It is worthwhile to highlight that >96% of the H 2 needs to be removed to shift equilibrium to the ethylene yield targets. Experimental work has been recently reported to better understand the consequences to the catalyst from operating conditions demanded by the membrane reactor concept, including higher olefin and lower H 2 partial pressures . These results indicated that achievement of equilibrium conversion may not be feasible with the current catalysts in use.…”
Section: Case Study: Ethane Dehydrogenationmentioning
confidence: 98%
“…It is worthwhile to highlight that >96% of the H 2 needs to be removed to shift equilibrium to the ethylene yield targets. Experimental work has been recently reported to better understand the consequences to the catalyst from operating conditions demanded by the membrane reactor concept, including higher olefin and lower H 2 partial pressures . These results indicated that achievement of equilibrium conversion may not be feasible with the current catalysts in use.…”
Section: Case Study: Ethane Dehydrogenationmentioning
confidence: 98%
“…The permeation experiments indicate the H 2 /C 3 H 8 separation factor increases with higher temperature and reaches >3 at 600 °C . On the other hand, the undesired cracking and coke reactions would be also accelerated under the H 2 -deficient atmosphere . In this context, integrating a H 2 -permeable membrane and appropriate active species is promising for improving the propylene yield in industrial applications.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Potential active species for this technology are Pt and Co, which show higher propylene selectivity and anticoking capacity compared to other elements as summarized in Tables –. Moreover, future H 2 -permeable membrane PDH technology should carefully optimize the H 2 -permeable levels, which not only assess the thermodynamic advantages due to H 2 removal but also consider the cracking and coking reactions in H 2 deficient conditions …”
Section: Summary and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The shale gas revolution has significantly lowered the cost of C 2 H 6 and stimulated great interest in exploiting its potential as a direct feedstock for C 2 H 4 production in recent years. Non-oxidative dehydrogenation of C 2 H 6 to C 2 H 4 has been considered as the potential route of the highest efficiency of carbon utilization; [5][6] however, it is still lack of efficient catalysts with high activity and stability in the high-temperature operation. As a case study, we therefore fabricate PSC α-Al 2 O 3 monolith with oxygen defects and explore their functionality towards non-oxidative dehydrogenation of C 2 H 6 to C 2 H 4 reaction.…”
Section: Introductionmentioning
confidence: 99%